Epicardial Surgical Ligation of the Left Atrial Appendage is Safe, Reproducible, and Effective by Transesophageal Echocardiographic Follow-up. Issue 5 (June 2013) - Zapolanski, Alex; Johnson, Christopher K.; Dardashti, Omid; O'Keefe, Ryan M.; Rioux, Nancy; Ferrari, Giovanni; Shaw, Richard E.; Brizzio, Mariano E.; Grau, Juan B.
Objective: The left atrial appendage (LAA) is the source of 90% of thrombi in patients with atrial fibrillation. Our double LAA ligation (LLAA) technique was shown to be 96% successful in a small study. However, the outcomes of these patients have yet to be compared with a set of nonligated patients. Methods: From 2005 to 2012, a total of 808 patients received LAA using our double ligation technique using both a polydioxanone (PDS) II endosnare and a running 4-0 Prolene pledgeted suture. The 30-day outcomes of these patients were compared with that of nonligated patients. Fifty-six of the ligated patients had a postoperative transesophageal echocardiography (TEE). An echocardiographer reviewed the follow-up TEEs for LAA remnant and/or residual flow into the LAA using color Doppler imaging. The patients with LAA flow and/or remnant depth of 1 cm or greater were deemed to have an unsuccessful exclusion. Results: The ligated group had a trend of less postoperative atrial fibrillation (19.4% vs 22.9%, P = 0.07) and an overall significantly lower in-hospital mortality (0.7% vs 3.0%, P < 0.001) and lower 30-day mortality (0.7% vs 3.4%, P < 0.0001). The LAA was successfully excluded in 53 (94.7%) of the 56 patients with TEE. Conclusions: Double LAA ligation correlates with lower rates of in-hospital and 30-day mortality. This advantage comes without an increase in perioperative complications. This technique can easily be performed off or on pump, is very reproducible, and comes at a very low cost compared with LAA occlusion devices. Stroke has a multifactorial etiology; successful LLAA removes one potential source of thrombi perioperatively and in the long-term.